Self-administered tuberculosis treatment outcomes in a tribal population on the indo-myanmar border, Nagaland, India. - Mrinalini Das; Petros Isaakidis; Rahul Shenoy; Rey Anicete; Hemant Kumar Sharma; Imyangluba Ao; Kaikho Osah; Homa Mansoor; Peter Saranchuk; Sunita Abraham (PLoS ONE, 2014)
BACKGROUND: Multiple strategies are being adopted by national tuberculosis (TB) programmes to achieve universal coverage of tuberculosis treatment. However, populations living in 'hard-to-reach' areas of north-east India have poor access to health services. Our study aimed to detail treatment outcomes in TB program supported by Médecins Sans Frontières (MSF) and using an alternative model of TB treatment delivery in Mon district, Nagaland, India. METHODS: This was a retrospective cohort study of TB patients, initiated on self-administered therapy (SAT) through Mon District Hospital, Nagaland, India between April 2012 and March 2013. RESULTS: A total of 238 tuberculosis patients had final TB treatment outcomes during the study period, including 82 and 156 from semi-urban and rural areas respectively. The majority of patients (62%, 147/238) were suffering from pulmonary, smear-positive tuberculosis. Overall, 74% of patients (175/238) had successful outcomes, being cured or having completed their treatment. Females (81%), pulmonary TB patients (75%) and those on a Category I regimen (79%) had better treatment success rates than males (67%), extra-pulmonary TB patients (62%) and patients on a Category II regimen (61%). The univariate and bivariate analyses found age, sex and TB treatment regimen significantly associated with unsuccessful TB treatment outcomes (defined as death, loss-to-follow-up and failure). However, only older age showed significance in a multivariate binary logistic regression model. CONCLUSION: Our study suggests that self-administered TB treatment is feasible for patients living in areas with limited or no access to health services. The relatively low number of patients with adverse outcomes suggests that SAT models are safe; other advantages include the need for fewer resources and less frequent movements by patients. National TB programmes should consider allowing SAT strategies for delivery of TB treatment to 'hard-to-reach' populations, which could in turn help to achieve universal coverage and contribute to global TB elimination by 2050.